Wafer curvature, temperature inhomogeneity, plastic deformation and their impact on the properties of GaN on silicon power and opto‐electronic structures. Issue 3 (28th January 2014) - Schulz, Oliver; Dadgar, Armin; Hennig, Jonas; Krumm, Oliver; Fritze, Stephanie; Bläsing, Jürgen; Witte, Hartmut; Diez, Annette; Krost, Alois
Abstract: A high device production yield requires accurate strain engineering during the epitaxial growth by different reasons. The maximum usable wafer area for subsequent processing is reached for zero curvature at room temperature. Besides this production process fact, the homogeneity of the growth demands a constant growth regime across the whole wafer, especially for ternary or quaternary compounds. Due to the dominant mismatch of the thermal expansion, these factors are of special importance for the growth of GaN devices on Silicon wafers. This work presents a step‐by‐step analysis of the correlation between in‐situ growth monitoring results (temperature, growth rate, and curvature) and the layer properties of power‐ and opto‐electronic device structures. Several methods as XRD, PL and electrical measurements are used to prove this relationship. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)